Hyperemesis gravidarum and neonatal outcomes: A systematic review of observational studies - Pinelopi Varela; Anna Deltsidou (Elsevier, 2021)
Hyperemesis gravidarum (HG) is associated with adverse somatic and psychological effects. The impact of HG on neonatal outcomes is debatable given that disagreeing research results have appeared. The objective of this study was to systematically review, according to the PRISMA guidelines, and synthesize the available evidence from observational studies on the relationship between HG and neonatal outcomes. The PubMed, Scopus, and Science Direct databases were systematically reviewed, with the last search carried out in April 2020. The quality of the studies was estimated using the Newcastle-Ottawa Scale (NOS) for non-randomized studies. The databases search yielded 516 studies 15 of which (n = 112.372 HG cases) matched eligibility criteria while the majority of the studies were of moderate quality (n = 12). We observed heterogeneity among the studies regarding the definition of HG and characteristics of the samples. The results of this systematic review suggest that it is still uncertain whether HG has an adverse impact on neonatal outcomes, fact that requires more studies to be conducted.